The Relationship between Work Stress and Workplace Deviant Behaviours in the Nigerian Banking Industry - Adekanmbi, Foluso Philip; Ukpere, Wilfred I. (Journal of Reviews on Global Economics, 2019)
This paper focuses on examining the relationship between work stress and workplace deviant behaviours in the Nigerian banking industry. Hence, the paper plans to propose ways of reducing work stress in the workplace, which will consequently reduce workplace deviant behaviours in the workplace, particularly within the Nigerian banking industry. However, the current study adopted a quantitative research approach, a survey research design. In addition, one non-probability sampling method and two sampling approaches were used, namely purposive stratified and simple random sampling, respectively. The findings revealed that work stress has a statistically positive significant relationship with workplace deviant behaviours in the Nigerian banking industry. Moreover, the results of this investigation have major implication for organisational behaviour, managerial decisions, and harmonious employee employment relationship in the Nigerian banking industry. Increased work stress significantly increases workplace deviant behaviours in the Nigerian banking industry. Hence, the Nigerian banking industry can minimise workplace deviant behaviours through a decrease or reduction in the level of work stress. There have been little, if any studies done to ascertain the relationship between work stress and workplace deviant behaviours in the Nigerian banking industry. The current investigation noticed a significant moderate positive relationship between work stress and workplace deviant behaviours in the Nigerian banking industry, indicating that the Nigerian bank employees will engage more in deviant behaviours if they encounter an increased levels of work stress in the Nigerian banking industry, as well as engage less in deviant behaviours in proportion to the low levels of work stress encountered.